PEMBINAAN UMAT HINDU PASCA SUDHI WADANI DI KECAMATAN BATURITI KABUPATEN TABANAN (Perspektif Teologi Sosial) - I Made Gami Sandi Untara (Jnanasidanta, 2021)
Sudhi Wadhani is a ceremony for someone who will embrace Hinduism. Sudhi Wadani is usually performed before the wedding ceremony. The Sudhi Wadani ceremony is an inauguration ceremony or ratification and promise of someone who was not previously Hindu to become a Hindu religion follower based on sincerity without coercion. Guidance or education for Hindus after Sudhi Wadani is very necessary. It aims to provide basic knowledge of Hindu teachings and prevent reconversion. This type of research is a qualitative research using a phenomenological approach. The primary data sources in this study were the people who were in Sudhi Wadani, and community leaders. The implications of social theology for the development of post-Sudhi Wadani Hindus, Baturiti District, include increasing appreciation and practice of post-Sudhi Wadani Hindu religious teachings, increasing the adaptability of post-Sudhi Wadani people to the surrounding social environment which is reflected in the active interaction of the post-Sudhi Wadani people and the sense of telerance that exists. tall. Then the people also feel psychologically comfortable being Hindus as a whole, which is reflected in their belief and sincerity to serve their ancestors. As well as the strengthening of Hindu religious education both formally and non-formally thanks to the role of all parties involved in it  Keywords: Sudhi Wadani, Social Theology, Coaching